Dietary interventions through supplementation with antioxidant compounds - Todorović, Vanja; Djordjević, Brižita (Archives of Pharmacy, 2023)
Dietary supplements (DS) are manufactured products consisting of one or more dietary ingredients; they are intended to supplement the diet and provide additional nutrients or other beneficial compounds that are lacking or insufficient in a regular diet. Dietary supplements containing antioxidant compounds have been shown to have positive effects in various (pato)physiological processes, i.e., any condition that is fundamentally redox imbalanced (cardiovascular diseases, cancer, aging, intense exercise). The most common antioxidants in dietary supplements are clearly antioxidant micronutrients such as vitamin C, vitamin E, zinc, and selenium, but also various secondary plant compounds, including polyphenols and carotenoids. The dosage of antioxidants administered through dietary supplements may not always be optimal, so some dietary interventions through supplementation with antioxidant compounds have been shown to have an effect that it is limited, or completely absent. Therefore, any dietary supplementation should be done only under appropriate guidance from health care professionals to ensure that it is safe, effective, and appropriate for the individual’s condition and needs.